The effect of early postpartum administration of intrauterine povidone-iodine on the postpartum period in Holstein cows - Ürer, EK; Fındık, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Uterine diseases mostly caused by bacterial contamination after parturition. We are aimed to reduce the intrauterine bacterial load and spontaneously occurring postpartum (pp) involution problems, enhance the involution process, retaining fertility parameters on physiological and economical limits by intrauterine povidone iodine solution in early pp. Study group (SG, n=34) was administered 100 ml povidone-iodine in 2% dilution while Control group (C, n=35) was administered 100 ml 0.9% NaCl solution intrauterine within 24 hours pp. After intrauterine administrations placental expulsion time and placental retention noted down. Rectal temperature measured for 8 days. Vaginal, rectal and USG examinations were done five day intervals starting from pp day 5 up to pp 40th days. Vaginal discharge character and odour examined vaginally; cornu and cervix uteri diameters measured by USG. Microbiological samples were taken twice, on 15th day’s pp and on the day of first estrus. Involution period, pp uterine infections were noted down. First insemination pregnancy rate, second insemination pregnancy rate, third insemination pregnancy rate and insemination index were evaluated up to 80, 150 and 400 days pp in groups. There were no statistically differences on any parameters examined. It is concluded that the use of intrauterine povidone iodine on early pp period has no preventive effect on reproductive performance. On the other hand it has no detrimental effect either. Therefore the use of intrauterine povidone iodine in early postpartum period considered to be ineffective.